Efficacy of Subcutaneous Methotrexate in JIA Patients Who have Failed to Improve with Oral Methotrexate (Bangladesh Journal of Child Health, 2012)
Objective: To determine the efficacy of subcutaneous methotrexate in patients with juvenile idiopathic arthritis (JIA) who failed to improve with oral methotrexate according to American College of Rheumatology 30 (ACR 30) improvement criteria. Design: Interventional Study. Setting: Rheumatology follow up clinic, Department of paediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, during the period from July 2006 to December 2008 . Methods: Twenty five patients who failed to improve with oral methotrexate were switched to subcutaneous methotrexate. Dose of methotrexate were same in both oral and subcutaneous route, at a dose of 10 mg/m2/week as a single dose. Results: According to ACR 30 criteria 76% patients improved after switching over to subcutaneous route. Among the core set variables active arthritis had the highest percentage of improvement and laboratory criteria (ESR) showed lowest improvement. Conclusion: From this study it may be concluded that subcutaneous methotrexate could be effective in patients with JIA who failed to improve with oral methotrexate. DOI: http://dx.doi.org/10.3329/bjch.v35i1.10368 BJCH 2011; 35(1): 16-19